Spatial distribution of the black coral Leiopathes glaberrima (Esper, 1788) (Antipatharia: Leiopathidae) in the Mediterranean: a prerequisite for protection of Vulnerable Marine Ecosystems (VMEs). Issue 1 (1st January 2018) - Massi, D.; Vitale, S.; Titone, A.; Milisenda, G.; Gristina, M.; Fiorentino, F.
Abstract: Leiopathes glaberrima is an important component of the deep coral forests of the Mediterranean Sea enhancing benthic biodiversity and forming an essential habitat for many marine organisms. It is a sessile species with high longevity; it is therefore highly affected by fishing impacts and has been listed as a representative taxon of Vulnerable Marine Ecoystems (VMEs). Since information on spatial distribution of L. glaberrima is still scanty and fragmented, an updated synopsis of its distribution in the Mediterranean is given, including two new records in the Strait of Sicily. On the basis of this updated information, hotspots of black coral off the Carloforte Island in the Sardinian Sea, on the Marco Bank and off the Pontine Islands in the Southern Tyrrhenian Sea, and on the Malta Graben in the Strait of Sicily are proposed for implementation of Fishery Restricted Areas.